THE STUDENTS’ DIFFICULTIES IN LEARNING ENGLISH AT MADRASAH IBTIDAIYAH TEACHER EDUCATION STUDY PROGRAM - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Jurnal Serunai Bahasa Inggris, 2021)
English is one of compulsory subjects that must be learned by students of elementary school to collage level. In fact, some students have difficulty in learning English. This study aims to describe the factors affect students’ difficulties in learning English. The subjects of the study were 30 students of the Madrasah Ibtidaiyah Teacher Education Study Program at Universitas Islam Negeri Sumatera Utara. This study applied a qualitative descriptive research with a questionnaire and observation instruments. The data analysis of this study used interview, observation, documentation and triangulation. The researchers found that there are two difficulties factors in learning English particularly internal factors and external factors, including 1) students’ low motivation; 2) lack of understanding of the importance in learning English (3) lack of opportunities to learn English (4) Lack of environment supports such as parents, friends, etc.Keywords: Learning difficulties, factors of difficulties in learning English